2016
DOI: 10.1021/acs.jpclett.6b01452
|View full text |Cite
|
Sign up to set email alerts
|

Extended Photo-Conversion Spectrum in Low-Toxic Bismuth Halide Perovskite Solar Cells

Abstract: Lead-based perovskites show very promising properties for use in solar cells; however, the toxicity of lead is a potential inhibitor for large-scale application of these solar cells. Here, a low-toxic bismuth halide, CsBi3I10, is synthesized from solution and the optical properties and crystal structure are compared with previously reported Cs3Bi2I9 perovskite, and the photovoltaic properties are also investigated. The XRD pattern suggests that the CsBi3I10 film has a layered structure with a different dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
207
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 28 publications
16
207
0
Order By: Relevance
“…e) Photo and SEM images of Cs 3 Bi 2 I 9 (left) and CsBi 3 I 10 (right). Reproduced with permission 100. Copyright 2016, ACS.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…e) Photo and SEM images of Cs 3 Bi 2 I 9 (left) and CsBi 3 I 10 (right). Reproduced with permission 100. Copyright 2016, ACS.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
“…CsBi 3 I 10 : Johansson et al100 reported another type of cesium bismuth iodine compound CsBi 3 I 10 . In contrast to previously reported Cs 3 Bi 2 I 9 , CsBi 3 I 10 has a different orientation of crystal growth, which may explain a more uniform and smoother coverage on TiO 2 .…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
“…An EQE of 80% exceeds the highest previously reported for BiOI [18] and is higher than recently reported EQEs from other bismuth halides and chalcohalides (discussed in the Introduction). [10,14,42] We found that we could further improve efficiency by lowering the deposition temperature of ZnO from 100 to 80 °C. This led to a reduction in the dark current densities (Figure 4a) and an increase in the reverse-sweep fill factors from 32 ± 2 to 39 ± 3%.…”
mentioning
confidence: 97%
“…[1] The short-circuit current densities (J SC , <4 mA cm −2 ) and external quantum efficiencies (EQEs, <60%) have also been poor, [1,18] in spite of efforts to extend the photoconversion range of bismuth halide semiconductors (J SC < 3.4 mA cm −2 , EQE < 25%). [14] Although higher efficiencies have been reported in bismuth-and antimony-based chalcogenides, [19][20][21][22] it is important to understand whether the broader range of ns 2 compounds predicted to be defect-tolerant could also exceed 1% power conversion efficiency and reach the levels needed for commercial production after optimization.…”
mentioning
confidence: 99%
“…76 Furthermore, common additives, such as 4-tert-butylpyridine, can dissolve the absorber. 89 Organic materials are also prone to degradation (potentially limiting device lifetime), are expensive, 90,91 and have been found to be the source of failure in fracture toughness testing. 92 For electron transport layers, bismuth-based photovoltaics commonly use n-type oxides, such as TiO 2 , SnO 2 , and ZnO, which have given the most efficient lead-halide perovskite devices.…”
Section: Contacts and Device Performance For Bismuth-based Photovmentioning
confidence: 99%